2022
DOI: 10.3390/jpm12122003
|View full text |Cite
|
Sign up to set email alerts
|

Admissions to the Emergency Department Due to Atrial Fibrillation/Atrial Flutter Incidents during the Third Wave of COVID-19 Pandemic

Abstract: (1) Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection increases the risk of atrial fibrillation/flutter (AF/AFL) incident. The study aimed to present the characteristics of admissions to the emergency department (ED) due to AF/AFL incidents during the third COVID-19 pandemic wave. (2) Methods: A retrospective analysis of the medical records of the ED patients: 8399 during 3 months of the second and 11,144 during the 3 months of the third pandemic wave. (3) Results: SARS-CoV-2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This high risk of AF in patients admitted with COVID-19 has been related to different mechanisms, including hypoxia (particularly in case of diffuse lung infiltration), inflammatory state, direct myocardial injury (ischemia, inflammation, etc), abnormal host immune response, or some drugs, among others.. [21][22][23][24] In fact, AF, including new-onset AF, has been described as the most common cardiac event associated with hospitalization for COVID-19. [25][26][27] Although we included our patients during the first wave of COVID-19 pandemic, recent studies have shown that AF incidence is also increased in the subsequent waves of COVID-19 infection, 28 indicating that our data are current.…”
Section: Discussionmentioning
confidence: 99%
“…This high risk of AF in patients admitted with COVID-19 has been related to different mechanisms, including hypoxia (particularly in case of diffuse lung infiltration), inflammatory state, direct myocardial injury (ischemia, inflammation, etc), abnormal host immune response, or some drugs, among others.. [21][22][23][24] In fact, AF, including new-onset AF, has been described as the most common cardiac event associated with hospitalization for COVID-19. [25][26][27] Although we included our patients during the first wave of COVID-19 pandemic, recent studies have shown that AF incidence is also increased in the subsequent waves of COVID-19 infection, 28 indicating that our data are current.…”
Section: Discussionmentioning
confidence: 99%